2019
DOI: 10.17533/udea.redin.20190517
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and characterization of PV module defects by thermographic inspection

Abstract: Being able to detect, to identify and to quantify the severity of defects that appear within photovoltaic modules is essential to constitute a reliable, efficient and safety system, avoiding energy losses, mismatches and safety issues.  The main objective of this paper is to perform an in-depth, onsite study of 17,142 monocrystalline modules to detect every single existing defect, classifying them in different groups, studying the variance of the same kind of defect in different modules and the patterns of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…FLIR Systems, model ThermaCAM S60 has been the IR thermography used. According to [24] and [25], images resolution obtained in a terrestrial thermographic inspection were better than those obtained in aerial thermographic, which has allowed obtaining better results.…”
Section: Methodsmentioning
confidence: 98%
“…FLIR Systems, model ThermaCAM S60 has been the IR thermography used. According to [24] and [25], images resolution obtained in a terrestrial thermographic inspection were better than those obtained in aerial thermographic, which has allowed obtaining better results.…”
Section: Methodsmentioning
confidence: 98%
“…Electroluminescence can also be performed by a UAV survey (Vidal De Oliveira et al, 2019, Alves Dos Reis Benatto et al, 2020, although is it not yet clear how to practically achieve 100% module coverage for a utility-scale site due to the requirement of powering each module (Gallardo-Saavedra et al, 2019).…”
Section: Automating Visual-based Inspectionmentioning
confidence: 99%
“…Research works that analyze failure mode in solar modules, e.g., Refs. [5][6][7][8][9][10][11], have identified that the power reduction in PV modules under fault causes a deformation of the current-voltage curve, e.g., curves in [12].…”
Section: Introductionmentioning
confidence: 99%